Patient Blood Management is Associated With a Substantial Reduction of Red Blood Cell Utilization and Safe for Patient's Outcome: A Prospective, Multicenter Cohort Study With a Noninferiority Design. Issue 2 (August 2016) - Meybohm, Patrick; Herrmann, Eva; Steinbicker, Andrea U.; Wittmann, Maria; Gruenewald, Matthias; Fischer, Dania; Baumgarten, Georg; Renner, Jochen; Van Aken, Hugo K.; Weber, Christian F.; Mueller, Markus M.; Geisen, Christof; et al.
Abstract : Objective: To determine whether the implementation of patient blood management (PBM) is effective to decrease the use of red blood cell without impairment of patient's safety. Background: The World Health Organization encouraged all member states to implement PBM programs employing multiple combined strategies to increase and preserve autologous erythrocyte volume to minimize red blood cell transfusions. Data regarding safety issues are not sufficiently available. Methods: In this prospective, multicenter study, surgical inpatients from four German University Hospitals were analyzed before (pre-PBM) and after the implementation of PBM. PBM program included multiple measures (ie, preoperative optimization of hemoglobin levels, blood-sparing techniques, and standardization of transfusion practice). Primary aim was to show noninferiority of the PBM cohort with a margin of 0.5%. Secondary endpoints included red blood cell utilization. Results: A total of 129, 719 patients discharged between July 2012 and June 2015 with different inclusion periods for pre-PBM (54, 513 patients) and PBM (75, 206 patients) were analyzed. The primary endpoint was 6.53% in the pre-PBM versus 6.34% in the PBM cohort. The noninferiority aim was achieved ( P < 0.001). Incidence of acute renal failure decreased in the PBM cohort (2.39% vs 1.67%; P < 0.001, regression model). The mean number of red blood cell transfused per patient was reduced from 1.21 ± 0.05 to 1.00 ± 0.05 (relative change by 17%, P < 0.001). Conclusions: The data presented show that implementation of PBM with a more conscious handling of transfusion practice can be achieved even in large hospitals without impairment of patient's safety. Further studies should elucidate which PBM measures are most clinically and cost effective. Trial Registration: PBM-Study ClinicalTrials.gov, NCT01820949 Abstract : Supplemental Digital Content is available in the text